Quaid-i-Azam Mohammad Ali Jinnah - Jinnah, Mohammad Ali (Islamabad Govt. of Pakistan, Ministry of Information & Broadcasting, Directorate of Films & Publications, 1976)
This book is an enlarged edition of the speeches, statements, interviews, Press Conferences and messages of Quaid-I-Azam Mohammad Ali Jinnah delivered or issued from June 3, 1947 to August 27, 1948.
Include Illustrations
Quaid-i-Azam Mohammad Ali Jinnah : Speeches and Statements as Governor General of Pakistan, 1947-1948.
Keywords: Pakistan -- Politics and government -- India -- Jinnah, Mahomed Ali, 1876-1948